(untitled) (Journal of Asian Development Studies, 2024)
Spina bifida is an inborn abnormality that causes the spinal column to be split because the developing brain tube fails to shut during the fourth week of development. Caring for a child with Spina Bifida is a demanding and time-consuming responsibility that often requires parents to reassess their goals and priorities, leading to increased stress. As the implications of having a child with Spina Bifida on parents are varied and vast, the current study attempts to fill a gap in prior research by addressing the significance of the relationship between a sense of coherence, marital satisfaction, and the moderating role of hope. The current study was based on cross-sectional survey research. Data were collected with snowball sampling from parents with the age range between the ages of 25 years to 45 years from different hospitals located in Lahore and also online from social media groups. Findings revealed that parental stress is negatively related to marital satisfaction, and hope is positively associated with a sense of coherence. Hope also moderated the relationship between parental stress, sense of coherence, and marital satisfaction. The findings of this study will help to design social and moral support to facilitate such parents and enable them to face the challenges of parenting a child with SB.